2015
DOI: 10.1007/s10869-015-9410-0
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Situational Interviews Predict Performance? Is it Saying How You Would Behave or Knowing How You Should Behave?

Abstract: PurposeThe present study examined two theoretical explanations for why situational interviews predict work-related performance, namely (a) that they are measures of interviewees’ behavioral intentions or (b) that they are measures of interviewees’ ability to correctly decipher situational demands.Design/Methodology/ApproachWe tested these explanations with 101 students, who participated in a 2-day selection simulation.FindingsIn line with the first explanation, there was considerable similarity between what pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 55 publications
12
40
0
Order By: Relevance
“…However, as interviewees volunteered to take part in the study with the aim to gain first-hand experience of job interviews, there is reason to believe that they considered the procedure as a serious dry-run for a real job interview. This would also support evidence from other studies that used a similar approach and in which the vast majority of the participants indicated that they had acted and felt as in a real selection interview (e.g., Van Iddekinge et al, 2005 ; Jansen et al, 2013 ; Oostrom et al, 2016 ). Nevertheless, using a student sample may underestimate the differences between interview conditions since familiarity with modern communication technologies such as videoconferencing may have contributed to a lessening of concerns related to these technologies.…”
Section: Discussionsupporting
confidence: 82%
“…However, as interviewees volunteered to take part in the study with the aim to gain first-hand experience of job interviews, there is reason to believe that they considered the procedure as a serious dry-run for a real job interview. This would also support evidence from other studies that used a similar approach and in which the vast majority of the participants indicated that they had acted and felt as in a real selection interview (e.g., Van Iddekinge et al, 2005 ; Jansen et al, 2013 ; Oostrom et al, 2016 ). Nevertheless, using a student sample may underestimate the differences between interview conditions since familiarity with modern communication technologies such as videoconferencing may have contributed to a lessening of concerns related to these technologies.…”
Section: Discussionsupporting
confidence: 82%
“…This allowed us to collect all variables of interest in a setting that comes at least relatively close to actual selection interviews. Furthermore, previous research also revealed that interview performance ratings from interview simulations can be criterion valid for the prediction of performance in job simulations (Oostrom, Melchers, Ingold, & Kleinmann, 2016 ), of academic performance (Day & Carroll, 2003 ; Klehe & Latham, 2006 ), and of actual job performance (Ingold, Kleinmann, König, Melchers, & Van Iddekinge, 2015 ).…”
Section: Methodsmentioning
confidence: 98%
“…A set of structured interview questions was presented to the older adults within a hypothetical situation. Situational interviewing is a scenario-based technique where participants are presented hypothetical situations with the aim of predicting an individual’s performance and behavioral intentions [ 39 ]. Situational interviewing is based on the premise that intentions predict behavior, where an individual is asked to prospectively indicate how they would behave in a given situation [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%